Rol de las aves en el patrimonio cultural inmaterial de la parroquia Zumbahua, cantón Pujilí. provincia de Cotopaxi. - Mena Pacheco, Wendy Guissele (2022)
The purpose of this research project is to compile the functions that birds play in the cultural manifestations, for which it was developed in the situational area of the study, information was collected from primary and secondary sources which support the scientific development of the project, information was extracted that allows knowing the most relevant characteristics such as: trade, tourism and leisure activities, determining the little knowledge that exists in the community about the different cultural manifestations they have, since the loss of customs and traditions has not allowed the current generations not to know them. A thorough inventory of the existing cultural manifestations was developed through interviews and coexistence with the population, for which the elderly were taken as the main source of information to extract the knowledge resulting in 14 cultural manifestations in the parish of Zumbahua, developing the experiences obtained, to capture them in a formal record. The proposal is to develop a descriptive guide where all the information provided by each experience related by the elderly in the old generations is compiled, the same ones that are still in force today and we want to promote in the daily life of the current and future generations, so that they can be included in the cultural manifestations of the parish of Zumbahua current and future generations, so that the manifestations are culturalized and the importance of the role of the elderly is the importance of the role of birds as part of the Intangible Cultural Heritage.The descriptive guide is developed in two languages, Spanish and Kichwa that tells about the manifestations with the purpose of informing young people and children about the existing manifestations using tactics for its dissemination by the GAD of the parish of Zumbahua a record of the demonstrations who will be in charge , imparting the knowledge of the descriptive guide by the developing playful activities (theatrical plays) in the different educational institutions in order to make it attractive and easy to know, in addition to disseminate by technological means through the web page of the GAD of the parish the symbolic value that birds have in the Intangible Cultural Heritage of the Parish of Zumbahua.